me ajudem a resolver essa expressão numérica ?
![(y + \sqrt{5} ) {}^{2} - (y + \sqrt{5} ) \times (y - \sqrt{5} ) + (y - \sqrt{5} ) {}^{2} (y + \sqrt{5} ) {}^{2} - (y + \sqrt{5} ) \times (y - \sqrt{5} ) + (y - \sqrt{5} ) {}^{2}](https://tex.z-dn.net/?f=%28y++%2B++%5Csqrt%7B5%7D+%29+%7B%7D%5E%7B2%7D++-+%28y+%2B++%5Csqrt%7B5%7D+%29+%5Ctimes+%28y+-++%5Csqrt%7B5%7D+%29+%2B+%28y+-++%5Csqrt%7B5%7D+%29+%7B%7D%5E%7B2%7D+)
Soluções para a tarefa
Respondido por
2
Produtos notáveis:
(a + b)² = a² + 2ab + b²
(a - b)² = a² - 2ab + b²
(a + b)(a - b) = a² - b²
Vamos lá:
Resolvendo eles:
(y² + 2y.√5 + 5) - (y² - 5) + (y² - 2y√5 + 5) =
y² + 2y√5 - 5 - y² + 5 + y² - 2y√5 + 5 = anulando os opostos:
y² + 5
Bons estudos
(a + b)² = a² + 2ab + b²
(a - b)² = a² - 2ab + b²
(a + b)(a - b) = a² - b²
Vamos lá:
Resolvendo eles:
(y² + 2y.√5 + 5) - (y² - 5) + (y² - 2y√5 + 5) =
y² + 2y√5 - 5 - y² + 5 + y² - 2y√5 + 5 = anulando os opostos:
y² + 5
Bons estudos
Perguntas interessantes
Matemática,
11 meses atrás
Sociologia,
11 meses atrás
História,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Administração,
1 ano atrás
Filosofia,
1 ano atrás